2017
DOI: 10.3389/fmicb.2016.02116
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Interactions and Molecular Docking of Bile Salt Hydrolase (BSH) from L. plantarum RYPR1 and Its Prebiotic Utilization

Abstract: Prebiotics are the non-digestible carbohydrate, which passes through the small intestine into unmetabolized form, reaches the large intestine and undergoes fermentation by the colonic bacteria thus; prebiotics stimulate the growth of probiotic bacteria. Further, bile salt hydrolase (BSH) is an enzyme that catalyses the deconjugation of bile salt, so it has enormous potential toward utilizing such capability of Lactobacillus plantarum RYPR1 toward detoxifying through BSH enzyme activity. In the present study, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Although the study of the cause of these observations was without the objective of our experiment, it could be argued that this effect could be due to the differences in protein expression by this yeast due to pH and medium composition that, as has been already shown, could modify the composition of the yeast’s cell membrane and, thus, its interaction with intestinal cells [ 37 ]. Recent studies used molecular dynamics simulations suggest that components of medium could induce beneficial interaction between the probiotic and target cells [ 38 ]. Choi and Park [ 14 ] demonstrated that the composition of proteins and lipids of Pichia guilliermondii A9 differed when it was grown in a residue of the fermentation of kimchi or in yeast medium.…”
Section: Discussionmentioning
confidence: 99%
“…Although the study of the cause of these observations was without the objective of our experiment, it could be argued that this effect could be due to the differences in protein expression by this yeast due to pH and medium composition that, as has been already shown, could modify the composition of the yeast’s cell membrane and, thus, its interaction with intestinal cells [ 37 ]. Recent studies used molecular dynamics simulations suggest that components of medium could induce beneficial interaction between the probiotic and target cells [ 38 ]. Choi and Park [ 14 ] demonstrated that the composition of proteins and lipids of Pichia guilliermondii A9 differed when it was grown in a residue of the fermentation of kimchi or in yeast medium.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, there is growing evidence that some dietary substances, especially probiotics and prebiotics can modulate the gut microbiota of the host in a positive way and are therefore considered as important assets in the management of obesity. Various approaches such as omics methods, systems biology and metabolic engineering enable us to understand and optimize the metabolic processes (Yadav et al, 2016a,b). The major objectives of this review are to provide an overview of how prebiotics and probiotics modulate the gut microbiota in context of prevention or treatment of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Due to diverse beneficial bioactivities of health-related GABA, many researchers focused on how to synthesize high levels of GABA [ 7 ]. LAB is a developing field in food, yoghourt, beverage, and dairy food, and LAB have huge potential for GABA production in the food and pharmaceutical industry [ 8 , 9 ]. Lactobacillus plantarum [ 10 , 11 ], L .…”
Section: Introductionmentioning
confidence: 99%